Importance of Imidazolidinone Motif in 4-Phenyl-N-arylsulfonylimidazolidinone for their Anticancer Activity - Sharma, Vinay K.; Lee, Ki-Cheul; Joo, Cheon-Ik; Sharma, Niti; Jung, Sang-Hun (Bulletin of the Korean Chemical Society, 2011)
To investigate the possible isosteric replacement of imidazolidinone moiety in 4-phenyl-N-arylsulfonylimidazolidinone for broad and potent anticancer agents, a series of 4-phenyl-l(N)-arylsulfonylimidazolidinones 6ak,imidazolidinethione analogs 7a-i, and imidazolidine oxime analogs 8a-c were prepared and evaluated for their in vitro anticancer activity against four human cancer cell lines (human lung A549, human colon COLO205, human leukemia K562, human ovary SK-OV-3). Among all the derivatives of N-arylsulfonylimidazolidinone 6a-k, compounds 6f and 6g showed the best inhibition comparable to doxorubicin against all cancer cell lines. Increasing the carbon chain on alkyl moieties of carbamates as shown in 6c-g did not alter the activity. The imidazolidinethione analogs 7a-i and imidazolidin-2-one oxime derivatives 8a-c did not possess any good activity. Therefore, imidazolidinone moiety is the best pharmacophore among the 4-phenyl-Narylsulfonylimidazolidinone derivatives. KCI Citation Count: 4